Peningkatan Kemampuan Siswa Menulis Naskah Drama Menggunakan Model Pembelajaran Kooperatif Tipe STAD kelas VIIIA SMP Negeri 3 Tongauna - Alan (Cetta: Jurnal Ilmu Pendidikan, 2019)
The purpose of this study was to improve students' ability to write drama scripts using the STAD type cooperative learning model. This type of research is classroom action research. The method used is quantitative descriptive. The subjects of this study were students of class VIIIA SMP Negeri 3 Tongauna in the 2017/2018 school year consisting of 19 students. The instruments used in this study were test and nontest instruments. The ability of students in writing drama scripts refers to classical learning completeness and individual learning completeness. Students are said to complete learning if students get a value of 70, and said to be completed classically if at least 85% of students are able to achieve a value of 70.Based on the results of the study, the ability of VIIIA grade students at SMP Negeri 3 Tongauna in writing drama scripts using the STAD type cooperative learning model increased in each cycle. Starting with the ability of students in the pretest stage, the average value obtained was 64.03. Then an increase in cycle I to 74.56, and an increase in the second cycle to 84.21. The increase in the number of students who completed the pretest was only 7 students or 36.84%, then an increase in the first cycle to 13 students or by 68.42%, and increased again in the second cycle to 18 students or by 94.73%. From 19 students showed that their ability to achieve mastery value had reached 85%, with this it can be concluded that the use of STAD type cooperative learning models can improve students' abilities in writing drama scripts.